Preparation, characterisation and enhanced fungistatic properties of silicone rubber with different concentrations of CMIT/MIT - Shifang Yang; Zexuan Zhang; Qianpeng Hou; Yunpeng Liu; Chi Gong (High Voltage)
Abstract The authors explore the limitations of silicone rubber (SR) in tropical environments due to its lack of antimicrobial activity. The use of a 2‐methylisothiazol‐3(2H)‐one compound with 5‐chloro‐2‐methylisothiazol‐3(2H)‐one is proposed as an efficient and environmentally friendly antimicrobial agent to enhance the fungistatic properties of SR. The fungicide added specimen was obtained by directly adding a quantitative amount of isothiazolinone to the polymer system. Through an in‐depth analysis of the material properties of MCMSR, the form in which 2‐methyl‐4‐isothiazolin‐3‐one/5‐chloro‐2‐methyl‐4‐isothiazolin‐3‐one (MIT/CMIT) exists in the molecular structure of the SR crosslink system was carefully explored. The accelerated hydrolysis process of polysiloxane, which caused fungi secretion, was proven to be suppressed due to the effects of MIT/CMIT. The antimicrobial mechanism of isothiazolinone in preventing microbial growth was interpreted as the apoptosis and necrosis procedures of Aspergillus niger cells, which were verified by flow cytometry results. By choosing the appropriate concentration of isothiazolinone, the original properties of the SR were successfully maintained while effectively preventing the aggregation of isothiazolinone. This opens up a new research direction and application prospect for the antimicrobial modification of SR.